2005
DOI: 10.1158/0008-5472.can-04-3840
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Enhances whereas Tamoxifen Retards Development of Tsc Mouse Liver Hemangioma: A Tumor Related to Renal Angiomyolipoma and Pulmonary Lymphangioleiomyomatosis

Abstract: Pulmonary lymphangioleiomyomatosis and abdominal angiomyolipoma are related lesions for which there is no authentic animal model. Both of these proliferative lesions occur in sporadic patients, and at much higher frequency in patients with tuberous sclerosis, which is due to mutations in the TSC1 and TSC2 genes. Tsc1 +/À À and Tsc2 +/À À mice frequently develop liver hemangioma. We found that the Tsc mouse liver hemangioma are composed predominantly of endothelial cells but with a smooth muscle component, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Others have shown that oestrogen can stimulate proliferation of angiomyolipoma derived cells (Yu et al 2004) and angiomyolipoma related tumours (El-Hashemite et al 2005). Similarly, we have shown that oestrogen can stimulate AML cell growth to a similar degree to PDGF; although it is not clear whether this is a direct or indirect effect of oestrogen.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Others have shown that oestrogen can stimulate proliferation of angiomyolipoma derived cells (Yu et al 2004) and angiomyolipoma related tumours (El-Hashemite et al 2005). Similarly, we have shown that oestrogen can stimulate AML cell growth to a similar degree to PDGF; although it is not clear whether this is a direct or indirect effect of oestrogen.…”
Section: Discussionsupporting
confidence: 53%
“…Although the most accurate model of TSC-related hamartoma developed, these lesions also develop in most female animals over 7 months (El-Hashemite et al 2005). Like these other model systems, the AML xenograft has phosphorylated S6K1 but also has the advantage of a relatively short natural history allowing experiments to be performed more quickly, possibly making it a useful tool for screening new therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor alpha is expressed in LAM cells and in angiomyolipoma cells from LAM patients (17), and estrogen has been shown to activate p42/44 MAPK and stimulate the proliferation of Tsc2-null ELT3 cells and TSC2-null angiomyolipoma cells (11). Estrogen has also been shown to enhance liver hemangioma development in Tsc2Ϯ mice (30). Despite these findings, the role of estrogen in LAM pathogenesis is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…14 In animal studies, tumors that are closely related to human angiomyolipomas have also been reported to grow with estrogen therapy and regress on tamoxifen. 15 In Hamster animal models, renal epithelial tumors have been shown to be inducible with estrogen. 16,17 Figure 1 Non-tumorous stromal proliferation, (a) subjacent to calyceal urothelial lining and between dilated collecting ducts in a benign kidney with hydronephrosis, (b) underlying the urothelium (MLS), adjacent to a clear cell renal cell carcinoma extending close to the pelvicalyceal system, and (c) surrounding a benign cyst in a case of acquired cystic disease of the kidney.…”
Section: Discussionmentioning
confidence: 99%